Improved Detection of preclinical Colorectal Liver Metastases by High Resolution Ultrasound including Molecular Ultrasound Imaging using the targeted Contrast Agent BR55 - Hackl, C.; Schacherer, D.; Anders, M.; Wiedemann, L. M.; Mohr, A.; Schlitt, H. J.; Stroszczynski, C.; Tranquart, F.; Jung, E. M. (Ultraschall in der Medizin - European Journal of Ultrasound, 2016)
Purpose: Aim of the present study was to investigate the sensitivity of high resolution ultrasound (HRU), standard contrast-enhanced ultrasound (CEUS) and CEUS using a novel vascular endothelial growth factor receptor 2 (VEGFR2)-targeted contrast agent for the detection of hepatic metastases in a mouse model of colorectal cancer using clinical standard technology.Materials and Methods: The human colon cancer cell line HT29, transfected with luciferase cDNA for in vivo bioluminescence monitoring, was injected intrasplenically into CB17.SCID mice. Mice were monitored weekly by bioluminescence and after 2 and 4.5 weeks by HRU and CEUS. Contrast media (untargeted BR1, targeted BR55) was applied and digital cine loops from the arterial phase (15 – 45 sec), portal venous phase (50 – 120 s) and late phases (3 – 5 min, 1hour) of the whole liver were analyzed. Data were correlated with postmortem histopathology.Results: Without contrast enhancement, lesions > 4 mm were reliably detected. After use of untargeted CEUS, lesions > 2 mm were reliably detected and enhanced rim vascularization and late-phase wash-out was shown. With BR55, lesions > 0.8 mm were reliably detected with excellent documentation of vascularization. A persistent contrast enhancement was seen > 30 min after injection. Contrast-enhancement patterns with BR55 significantly correlated with CD31 (R2 = 0.74) and VEGFR2-immunohistochemistry (R2 = 0.66).Conclusion: Detection of metastases by HRU and CEUS was earlier and more accurate than monitoring via bioluminescence. In vivo monitoring of hepatic micrometastases can thus be performed without prior modification of cancer cells using standard technology.
Keywords: abdomen; blood vessels; ultrasound